Mechanism of Seizure Termination - J Gordon Millichap (Pediatric Neurology Briefs Publishers, 2008)
Physiological mechanisms contributing to seizure termination and organized according to membranes, synapses, networks, and circuits are reviewed by researchers from Albert Einstein College of Medicine, and Montefiore Medical Center, Bronx, New York.